2020
DOI: 10.1088/1755-1315/475/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of cocoa pod husk phenolic extract against Escherichia coli for food processing

Abstract: Cocoa pod husk (CPH) which is a waste of cocoa plantation contains phenolic compounds which can be used as antibacterial agents. Phenolic compounds in CPH include phenolic acids, flavonoids and flavones. The aim of this study was to analyze the antibacterial activity of CPH extract whis was extracted by using Microwave-Assisted Extraction (MAE) method. Extraction using 96% ethanol solvent with a ratio of 1:4, 1:6 and 1:8 (w/v) for 2, 3 and 4 minutes, respectively. The extraction results with the highest total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In this study, TPC was measured as CPH ethanolic extract was reported to contain polyphenols, including phenolic acids such as salicylic acid, p-hydroxybenzoic acid, protocatechuic acid, and flavonoid, mainly catechin and (epi)gallocatechin. [12] These polyphenol compounds were reported for its ROS scavenging activities, which could interact with the ROS produced by blue light, although the exact mechanism has not been elucidated. [13] In a previous study, TPC value of CPH extract was estimated to be 49.54 ± 3.39 mg GAE/g extract.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, TPC was measured as CPH ethanolic extract was reported to contain polyphenols, including phenolic acids such as salicylic acid, p-hydroxybenzoic acid, protocatechuic acid, and flavonoid, mainly catechin and (epi)gallocatechin. [12] These polyphenol compounds were reported for its ROS scavenging activities, which could interact with the ROS produced by blue light, although the exact mechanism has not been elucidated. [13] In a previous study, TPC value of CPH extract was estimated to be 49.54 ± 3.39 mg GAE/g extract.…”
Section: Discussionmentioning
confidence: 99%
“…Total phenolic content (TPC) of the CPHE nanopowder was measured and have previously been reported [32]. The TPC of CPHE nanopowder is 453 mg GAE/g dw extract, and the in vitro study of antibacterial activity of the CPHE phenolic nanopowder showed a zone of inhibition against Eschericia coli at a concentration of 5 mg/mL.…”
Section: Cphe Extract Characteristicsmentioning
confidence: 94%
“…A similar thickness is important because the mechanical properties and mass-transport properties of the composite membranes were investigated from comparable morphological thickness of the membranes. Total phenolic content (TPC) of the CPHE nanopowder was measured and have previously been reported [32]. The TPC of CPHE nanopowder is 453 mg GAE/g dw extract, and the in vitro study of antibacterial activity of the CPHE phenolic nanopowder showed a zone of inhibition against Eschericia coli at a concentration of 5 mg/mL.…”
Section: Composite Membrane Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Avocado seed is a residue rich in tannin polyphenols, phenolic acids, and flavonoids, which are the most representative groups, and other polyphenols, such as: (+)-catechin, (−)-epicatechin, and 3-leucoanthocyanidins, which have demonstrated anti-inflammatory properties [28]. Cocoa pod husks contain polyphenols and phenolic acids, such as protocatechuic acid, p-hydroxybenzoic acid, and salicylic acid-flavonols and flavonoid compounds that allow them to be used as potential food preservatives and antioxidants [29].…”
Section: Determination Of Antioxidant Activity and Polyphenol Content...mentioning
confidence: 99%